Foreigners in Muscovy western immigrants in sixteenth and seventeenth century Russia - Dreher, Simon; Mueller, Wolfgang 1970- (Taylor & Francis, 2022)
Cover -- Half Title -- Title -- Copyright -- Contents -- European Immigration to Muscovy in the Early Modern Era: An Introduction -- Section 1 Immigration, settlement, and integration -- 1 From Individual Destinies to an Emergent Community: Latins in Sixteenth-Century Moscow -- 2 Back in Moscow: Repatriation of Muscovite Emigrants in the Political and Legal Culture of Sixteenth- and Seventeenth-Century Russia -- 3 Foreigners on Moscow's Housing Market: Legislation, Practices, and Administrative Handling of Foreign Residence Ownership in the Decades before Its Prohibition in 1652 -- 4 Muscovite Ideology and the "Other" in the Town: Articles of the 1649 Law Code and the Impact of Local Initiative -- Section 2 Interaction, conflict, and cooperation -- 5 Foreign Mercenaries and the Russian Population, 1631-1634: Conflict and Coexistence -- 6 The Jesuit Mission and the Local Catholic Community in Smolensk: The First Years after the Treaty of Eternal Peace 1686 -- 7 Perlustration: The Opening of Foreigners' Mail in Muscovy -- 8 Foreign Engineers, the Conquest of Azov, and the Building of Taganrog -- Section 3 Communication and perception -- 9 A Foreigner in Early Sixteenth-Century Muscovy: Duke Mikhail Glinskii at the Muscovite Court -- 10 Playing Chess with Boris Godunov and Living in a Guesthouse: Attitudes to Armenian Merchants in Early Modern Muscovy -- 11 Entrepreneurial Behaviour and Family Networks in Dutch Trade with Russia, 1590-1750 -- 12 Halfway between the Kremlin and the Sloboda: The Catholic Physician Carbonarius and the Social Networks of Foreign Specialists in Muscovy -- Appendix 1: Maps -- Appendix 2: Glossary -- Appendix 3: Acronyms and Abbreviations -- Notes on the Authors and Editors -- Index.